Investment Risks and Tools for Their Minimization - Lola Sobirzhova; Boymurodova Lobar Tursunbai kizi (European Journal of Life Safety and Stability (2660-9630), 2023)
The article examines the theoretical and practical aspects of making investment decisions and organizing risk management in the process of investment activity, and substantiates the need to develop an investment risk management system, which should proceed from the fact that risks can have a strategic and tactical basis. The authors pay special attention to tools aimed at minimizing investment risks, including methods for reducing them. The levels of implementation of assessing the effectiveness of investment risk management according to relevant indicators are proposed.